504PAVID200 neutralizes TGF-beta1 and -beta3, the principal immunosuppressive TGF-beta isoforms overexpressed by tumours, and sensitizes tumours to immune checkpoint inhibitors. (1st October 2019) - Gruosso, T; O'Connor, M; Denis, J -F; Figueredo, R; Koropatnick, J; Tremblay, G; Tikhomirov, I A
Abstract: Background: Resistance to immune checkpoint inhibitors (ICIs) is a major unmet medical need. The TGF-beta pathway is a key immunosuppressive mechanism that correlates with resistance to PD-1/PD-L1 inhibitors. TGF-beta acts by inhibiting the recruitment and activation of anti-tumor T-cells, either directly, or indirectly through its action on cancer-associated fibroblasts. AVID200 is a receptor ectodomain trap that was rationally-designed to inhibit with pM potency TGF-beta1 and -beta3, the principal oncogenic TGF-beta isoforms. Targeting these two isoforms with AVID200 has the potential to increase the number of patients that benefit from ICIs. Methods: The percent of patients exhibiting tumor over-expression (>30FPKM) of TGF-beta isoforms was analyzed in > 10, 000 samples from the CGA RNAseq data. The potency and selectivity of AVID200 and other clinical stage TGF-beta inhibitors was assessed using an A549 cell-based. The ability of AVID200 to enhance the tumor-cell killing activity of T-cells was evaluated in vivo in a syngeneic 4T1 cancer model. The ability of AVID200 to enhance T-cell infiltration and the efficacy of ICIs was assessed in EMT-6 and MC-38 cancer models. Results: Gene expression analysis revealed that TGF-beta1 is the predominant isoform expressed in solid tumors, with TGF-beta3 also being expressed in multiple tumor types. This indicates that it is important to target both ligand isoforms for maximal efficacy, particularly because TGF-beta 1 and 3 can functionally substitute for each other. In vitro, AVID200 exhibited the best potency (low pM) and selectivity for TGF-beta 1 & 3 vs TGF-beta 2 amongst the TGF-beta inhibitors tested. Having minimal activity on TGF-beta2 is desirable because TGF-beta2 is involved in cardiac homeostasis and the positive regulation of hematopoiesis. In vivo, AVID200 was shown to promote T-cell infiltration and to increase the anti-tumor activity of ICIs. Conclusions: In conclusion, AVID200 efficiently neutralizes TGF-beta 1 and 3, the main oncogenic isoforms, with best-in-class potency and sensitizes tumors to immune checkpoint blockade. The AVID200 Phase 1 study in patients with solid tumors is ongoing. Legal entity responsible for the study: Forbius (Formation Biologics). Funding: Forbius (Formation Biologics). Disclosure: T. Gruosso: Full / Part-time employment: Forbius (Formation Biologics). M. O'Connor: Leadership role, Licensing / Royalties, Full / Part-time employment, Officer / Board of Directors: Forbius (Formation Biologics). J. Denis: Full / Part-time employment: Forbius (Formation Biologics). R. Figueredo: Research grant / Funding (self): Forbius (Formation Biologics); Research grant / Funding (self): Trillium Therapeutics, Inc.; Research grant / Funding (self): Critical Outcome Technologies, Inc. J. Koropatnick: Licensing / Royalties: Sarissa Inc; Research grant / Funding (self): Forbius (Formation Biologics); Research grant / Funding (self): Trillium Therapeutics, Inc; Research grant / Funding (self): Critical Outcome Technologies, Inc. G. Tremblay: Licensing / Royalties: Alethia Biotherapeutics; Full / Part-time employment: Forbius (Formation Biologics). I.A. Tikhomirov: Leadership role, Shareholder / Stockholder / Stock options, Licensing / Royalties, Full / Part-time employment, Officer / Board of Directors: Forbius (Formation Biologics).